Peran Notaris Untuk Menentukan Hak dan Tanggung Jawab Ahli Waris dalam Perspektif Hukum Islam - Roselli Anjelina Lumbansiatar; Rahma Dhani Fitria Sinaga; Agatha Sofia Simanjuntak; Syuratti A Rahayu Manalu (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Inheritance law is a provision that regulates matters of property. If it is not regulated in detail, this will result in disputes within the family, even disputes will have very fatal consequences, even bloodshed between the family itself, sometimes because the influence of custom or law is still very strong. custom, namely by postponing the distribution of the heir's inheritance. To avoid this, rights are required that are recognized or granted by law and must also be attached to the person's responsibilities, if they are protected. Benefits or rights recognized or granted by law must also attach to the person's responsibilities. The method in this research is a qualitative method with a statutory approach and a conceptual approach where this writing examines statutory regulations and examines legal concepts contained in the articles contained in legal regulations, especially regarding the role of notaries in determining rights and responsibilities. the heir's responsibility from the perspective of Islamic law. In this case, the Notary has an important role in a will because they ensure its legality, validity and execution in accordance with the law. They help prevent inheritance from becoming available and ensure that the will's wishes are legally fulfilled.